The Politician and his Banker - Christa Hainz; Hendrik Hakenes (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
Should the European Union grant state aid through an institution like the European Investment bank? This paper evaluates the efficiency of different measures for granting state aid. We use a theoretical model with firms that differ in their creditworthiness and compare different types of subsidies with indirect subsidization through public banks. We find that, in a large parameter range, the politician prefers public banks to direct subsidies because they avoid windfall gains to entrepreneurs and they economize on screening costs. For similar reasons, they may increase social welfare relative to subsidies. One important prerequisite for this result is that public banks must not be allowed to fully compete with private banks. However, from a welfare perspective, a politician uses public banks inefficiently often.
urn:nbn:de:bvb:19-epub-13330-2
Keywords: G21; G38; H25; 330; public bank; development bank; state aid; subsidies; governance